An empirical framework to predict idiosyncratic risk in a time of crisis: Evidence from the restaurant industry. Issue 1 (11th January 2016) - Hua, Nan; Dalbor, Michael C.; Lee, Seoki; Guchait, Priyanko
Abstract : Purpose: The purpose of this study is to invoke prospect theory to construct an empirical framework to predict idiosyncratic risk, and argue that when a firm performs better than its benchmarks, the firm tends to play safe by avoiding firm-specific risk to maintain its satisfactory performance level, but when a firm performs worse than its benchmarks, the firm may become aggressive with taking more risks to achieve an increased level of performance. Design/methodology/approach: This study tested the relationships between restaurant firms' future idiosyncratic risk and the proposed firm financial characteristics. Heteroscedasticity- and autocorrelation-consistent (HAC) standard errors (Newey and West, 1994) were used to deal with potential problems of autocorrelations and heteroscedasticity. The standard error of residuals from the Fama-French three-factor model (Fama and French, 1993) was estimated to proxy for restaurant idiosyncratic risk. Findings: The main analysis reveals that five financial characteristics are significant predictors for restaurant firms' future idiosyncratic risk in accordance with the proposed, negative relationship based on the prospect theory. Practical implications: Managers may predict their competitors' future risk-taking behaviors using the current study's findings, which will provide competitive advantage in a highly competitive business environment that we have now. Also, in practice, restaurant investors may consider findings of this study in forecasting future risks of their portfolio to help evaluate and revise their portfolios. Originality/value: First, this is a new endeavor of its kind dealing with the restaurant industry, filling the void in the literature in predicting the risk-taking behavior of restaurant firms in a time of crisis. Second, this study forms a prediction model that establishes "predictive causality" (Diebold, 2001) motivated by prospect theory. Third, building upon prior research, this study comprehensively examines relationships between the firm characteristics that capture firm-specific strategies (Ou and Penman, 1989) and the idiosyncratic risk that are "associated with firm-specific strategies" (Luo and Bhattacharya, 2009) in a restaurant setting. Finally, the findings of this study bear significant implications for practitioners and other parties of interest.